Travel and Poetic Vocation. Diana Bellessi's Early Poetry Between Senses and Otherness (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
On a perspective that considers travel as an initiation to life and art in which the body and its senses play a central role, I propose an interpretation of the first two works by the Argentinian poet Diana Bellessi —Buena travesía, buena ventura pequeña Uli (1974) and Crucero Ecuatorial (1981) — as the expression of the search and finding of her own poetic vocation, thanks to the physical closeness to people that she was able to experience in her six-year-long trip through the two Americas. Her answer to the moral appeal proceeding from the other will be studied in light of the theoretical works by Bauman, Ricoeur, Blanchot, and the rhetorical feature of the same poems. In particular, in Buena travesía, buena ventura pequeña Uli, the other is manifested as a voice, breathing, rhythm, with interesting results in the stylistic treatment of the text. On the contrary, Crucero Ecuatorial reveals a calmer and more self-confident position. The “right distance” between poetic vocation and solidarity has been attained.
Keywords: Diana Bellessi; Travel; Initiation; Poetry; Other; Senses